HARA STATUS OF POTASSIUM Absorption IN PRODUCING PALM OIL PLANT IN PERLABIAN VILLAGE, KAMPUNG RAKYAT DISTRICT, LABUHANBATU SELATAN DISTRICT - Artisa Ainun; Hilwa Walida; Badrul Ainy Dalimunthe; Khairul Rizal (ZIRAA'AH MAJALAH ILMIAH PERTANIAN, 2021)
Potassium is a macro nutrient that can affect the quality and quantity of oil palm bunches as well as resistance to disease and drought stress. So far, testing the status of potassium nutrient uptake in people's plantations in Perlabian Village, Kampung Rakyat Labuhanbatu Selatan District has never been carried out. Fertilization and maintenance are carried out through knowledge from generation to generation, so it is important to have a study on the nutrient uptake status of potassium in oil palm leaves. This research was conducted using a free grid survey method at the semi-detailed survey level with a density of 100 meters. A total of 6 leaf samples were taken on the 17th leaf midrib and then rubbed with 70% alcohol and then put into the plastic sample for further testing in the laboratory of PT. Socfindo. The results showed that the potassium in leaf samples 1, 3 and 4 experienced deficiency and leaf samples 2, 5 and 6 were at the optimum. In oil palm plantations in smallholder plantations in Perlabian Village, Kampung Rakyat Subdistrict, it shows that the total K content of leaves is included in the optimum category.